2013
DOI: 10.1080/22311866.2013.782759
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Phytochemical Screening of some Zimbabwean Medicinal Plants

Abstract: Twelve (12) medicinal plants endangered and commonly used by communities and traditional medical practitioners in 5 districts of Zimbabwe were selected. Twenty methanol freeze dried plant extracts were screened for phytochemistry using thin layer chromatography (TLC) with detection by UV and reagent sprays. Phytochemical group investigations indicated presence of tannins (80 %), saponins (70 %), flavonoids and cardiac glycosides (40 %), anthraquinone derivatives and coumarins (25 %) and alkaloid (15 %).Antibac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…In Zimbabwe, a study was set up with the help of GEF/UNDP/MET (Ministry of Environment and Tourism) to carry out scientific laboratory studies on 50 extracts from 26 medicinal plants commonly used by communities to assess their conservation status in five selected districts from two regions of the country and to raise awareness of their importance and promote their sustainable use. Subsequently, we reported the antioxidant properties of extracts from these plant species [6] [7] as well as their antimicrobial and phytochemical properties [8] [9]. The laboratory studies confirmed the rationale for their use in traditional medical practice in line with other studies elsewhere to evaluate TMs targeted at finding alternative safer drugs to treat modern illnesses and to overcome growing resistance to infective agents.…”
Section: Introductionsupporting
confidence: 56%
“…In Zimbabwe, a study was set up with the help of GEF/UNDP/MET (Ministry of Environment and Tourism) to carry out scientific laboratory studies on 50 extracts from 26 medicinal plants commonly used by communities to assess their conservation status in five selected districts from two regions of the country and to raise awareness of their importance and promote their sustainable use. Subsequently, we reported the antioxidant properties of extracts from these plant species [6] [7] as well as their antimicrobial and phytochemical properties [8] [9]. The laboratory studies confirmed the rationale for their use in traditional medical practice in line with other studies elsewhere to evaluate TMs targeted at finding alternative safer drugs to treat modern illnesses and to overcome growing resistance to infective agents.…”
Section: Introductionsupporting
confidence: 56%
“…Becker et al [68] isolated a eudesmanolide-type sesquiterpene lactone, 3-oxoeudesma-1,4(15),11(13)-triene-12,6a-lide commonly called dehydrobrachylaenolide from the roots of D. anomala. Munodawafa et al [71] isolated saponins and tannins from D. anomala roots.…”
Section: Phytochemistrymentioning
confidence: 99%
“…The following activities have been reported from D. anomala including anthelmintic [58,72], anticancer [66,70], antihyperglycemic [73,74], anti-inflammatory [47], antimicrobial [26,28,71,[75][76][77], antioxidant [26,71,74,78,79], antiplasmodial [66,80], hepatoprotective [56,79], toxicity, and cytotoxicity [68,71,74,80,81].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…For example, the bark is used as a powerful astringent to treat diarrhea, heavy menstruation, nosebleeding, headache, stomachache, schistosomiasis, sores, and skin problems; the root is believed to cure malaria, blackwater fever and gonorrhea [6,24,28,35,36]. Research studies reveal promising results concerning their antibacterial [37][38][39], antifungal [38], anthelmintic [40,41], and HIV-1 reverse transcriptase inhibitory properties [38] ( Table 1). At the environmental level P. angolensis is able to establish nitrogen-ixing symbiosis with rhizobium bacteria and therefore relevant for soil fertilization.…”
Section: No Studies Reportedmentioning
confidence: 99%
“…Pterocarpus angolensis DC Antischistosomal [90] RAPD [79,80] Stem, stem bark, leaves: anthelmintic [40] Seeds: antibacterial [91] Stem bark: antibacterial and anti-inlammatory; lack of mutagenicity [92] Stem bark, leaves: anthelmintic, antibacterial, and cytotoxic [41] Antibacterial [93] Stem bark: antibacterial; epicatechin and derivatives identiied [37] Stem bark: antibacterial; leaves, stem bark: antifungal, HIV-1 reverse transcriptase inhibitory [38] Leaves, stem bark: anti-inlammatory [94] Stem bark, roots: antibacterial; tannins and saponins identiied [39] Colophospermum mopane (Benth. )…”
Section: No Studies Reportedmentioning
confidence: 99%